SWOT Analysis for Strategies to Improve SME Competitiveness: (A Case Study of “Syamsurya” Grocery Store in Wonorejo Village) - Galih Tri Prayoga; Adhi Bawono (Universitas KH. Abdul Chalim Mojokerto, 2026)
Syamsurya Grocery Store is a retail MSME located in Wonorejo Village that serves the daily needs of the surrounding community. However, the store faces serious challenges from the growing dominance of modern minimarkets and e-commerce. This intense competition demands that the grocery store enhance its competitiveness through the implementation of appropriate and targeted strategies. This study aims to identify strategies that can be applied by Syamsurya Grocery Store using a SWOT analysis approach, covering its strengths, weaknesses, opportunities, and threats. The research employs a descriptive qualitative method, with data collected through in-depth interviews with the owner of Syamsurya Grocery Store and direct observation of the store's operations. The analysis results show an IFAS score of 1.33 and an EFAS score of 1.07, positioning the store in Quadrant I (Aggressive). This position reflects a great opportunity to optimally leverage internal strengths and external opportunities. The strategies generated include utilizing its strategic location, developing customer loyalty programs, using social media, and improving operations through better stock management and more attractive product displays. This study demonstrates that appropriate SO and WT strategies can maintain the grocery store's competitiveness in the retail market. Moreover, this research also contributes theoretically to the application of SWOT analysis for MSMEs in the rural retail sector and offers suggestions for future studies.